2005
DOI: 10.1021/jp0559581
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Activity of Photoinduced Ti3+ Centers in Titanium Oxide Gels

Abstract: We report on the chemical activity of trapped electrons in wet titanium oxide gels. These electrons are generated under the band gap irradiation of gels in the spectral range between 3.25 and 4.4 eV and stored as Ti3+ centers that absorb in the visible. Chemical processes in photoirradiated gels are generally similar to those earlier reported in TiO2 colloids; however, peculiarities exist. In particular, a high internal surface of gels strongly enhances interface reactions. Measurements of UV-visible absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 23 publications
0
27
0
2
Order By: Relevance
“…One of the earliest studies on the electron trapping capacity by TiO 2 was done by Kormann et al [125], who suggested that up to 10% of the cation sites in a nanoparticle could be occupied as electron traps when ethanol was used as a hole trap and O 2 was absent. Similarly, the Kanaev group [537,540,567,568] measured trapping capacities of 7%-14% in TiO 2 gels. Ikeda et al [488] examined a variety of TiO 2 powders under colloidal conditions, and measured the electron trapping capacity using methylviologen (which readily reacts with Ti 3+ sites) in deaerated solutions rich in hole scavengers (methanol or triethanolamine).…”
Section: Electron Trappingmentioning
confidence: 96%
“…One of the earliest studies on the electron trapping capacity by TiO 2 was done by Kormann et al [125], who suggested that up to 10% of the cation sites in a nanoparticle could be occupied as electron traps when ethanol was used as a hole trap and O 2 was absent. Similarly, the Kanaev group [537,540,567,568] measured trapping capacities of 7%-14% in TiO 2 gels. Ikeda et al [488] examined a variety of TiO 2 powders under colloidal conditions, and measured the electron trapping capacity using methylviologen (which readily reacts with Ti 3+ sites) in deaerated solutions rich in hole scavengers (methanol or triethanolamine).…”
Section: Electron Trappingmentioning
confidence: 96%
“…A high quantum yield and much longer life of the Ti 3+ ions can be achieved in wet TiO 2 gels. Kuznetsov et al [67] reported that the quantum yield of Ti 3+ as high as 22-25% has been independently obtained from the absorption delay and extinction measurements. These Ti 3+ centers can be produced by the wet TiO 2 gels under the UV irradiation in the spectral range between 3.25 and 4.4 eV.…”
mentioning
confidence: 99%
“…It has been assessed that around 10 % of the Ti 4+ cations can act as electron traps [24]. The number of trapped electrons would be on the order of 0.1-3 nm À2 [19,25].…”
Section: Transport To the Surface Trapping Detrapping And Recombinmentioning
confidence: 99%